KONTRIBUSI KREATIVITAS BELAJAR TERHADAP KETERAMPILAN LITERASI MEMBACA SISWA SEKOLAH DASAR - sukmayasa, hendra (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Student creativity in learning activities is a very important thing to cultivate from an early age. Learning creativity is thought to have a strong impact on elementary school students' reading literacy skills. The aim of this research is to determine the contribution of learning creativity to the reading literacy skills of class IV students at SD Cluster III, Buleleng District. This research is an ex-post facto research with a Correlation Study Survey design. The population of this study was all students in class IV of SD Cluster III, Buleleng District, totaling 394 students. Meanwhile, the sample for this research was 196. The independent variable in this research was students' learning creativity, while the dependent variable was students' reading literacy skills. Data on students' learning creativity was collected using tests, while data on students' reading literacy skills was collected by studying documents owned by teachers at school. The data analysis method used in this research is quantitative descriptive analysis method and simple regression analysis. Based on the research that has been conducted, it is concluded that there is a significant contribution of learning creativity to students' reading literacy skills with a contribution of 44.1% and an effective contribution of 17%.